In-flight reconfiguration of lithium-ion cells aimed at extending flight times and range of electrically powered UAVs. Issue 3 (1st July 2019) - Zabunov, Svetoslav; Mardirossian, Garo
Abstract : Purpose: The purpose of this paper is to disclose a novel reconfiguration battery design suitable for electrically powered UAVs. Design/methodology/approach: A design of a reconfigurable battery module is presented. Test setup with prototype battery module is developed and described. Test results of measurements are shown and discussed. Findings: The results ascertain the benefits of implementing a reconfigurable battery in small electrically powered UAVs and specifically prove the efficiency of the proposed design. Originality/value: The proposed novel design is compared to previous work while advances from the latter and the gained advantages were established.